KONFLIK DAN INTEGRASI PENDIRIAN RUMAH IBADAH DI KOTA BEKASI - Adon Nasrullah Jamaludin (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2018)
Every religion teaches brotherhood, and do not want hostility. But in reality, in the midst of public life, religion often appears as a force that can lead to conflict. One of the conflicts that often occur between religious communities in the context of the establishment of houses of worship. The conflict became one of the motives and trigger strife and anarchy among religious communities, especially in Bekasi. His case is very varied, ranging from the issue of the establishment of a new house of worship until revocation of a license by the Municipal Government. But the case of the establishment of houses of worship there, Kota Bekasi has a unique case, which is the area of the conflict (rejection) and other areas that occur integration (reception). What is interesting and at the same time become the focus of this paper are the factors causing the emergence of the phenomenon of conflict (rejection) in urban areas (urban), and the phenomenon of integration (reception) in the village (rural), especially in the context of the establishment of houses of worship. Based on data obtained that both have each contributing factor both internal and external.